2021
DOI: 10.1007/s12070-021-02507-x
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory Dysfunction is Associated with More Severe Clinical Course in COVID-19

Abstract: To perform a quantitative olfactory test in positive COVID19 RT-PCR admitted patients and asymptomatic ones, to evaluate the association between hyposmia and disease severity. This is a Cross sectional study. Ninety-one patients including 68 inpatients and 23 asymptomatic healthcare workers with positive COVID-19 RT-PCRs. Methods: Demographics and clinical characteristics were collected. Iran Smell Identification Test (IR-SIT), a highly accurate 6-odorant test was used to evaluate the reliability of self-repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Histological samples from the nose and immunohistochemical staining of the trigeminal nerve branches in SARS-CoV-2 infected persons may provide more detailed information. Of note, there is increasing evidence that patients with an affection of the nasal senses could have a more severe course of the disease [27] or more neurological symptoms [28].…”
Section: Discussionmentioning
confidence: 99%
“…Histological samples from the nose and immunohistochemical staining of the trigeminal nerve branches in SARS-CoV-2 infected persons may provide more detailed information. Of note, there is increasing evidence that patients with an affection of the nasal senses could have a more severe course of the disease [27] or more neurological symptoms [28].…”
Section: Discussionmentioning
confidence: 99%
“…length of stay, intensity of medical care, complicated versus noncomplicated). Five studies [16][17][18][19][20] reported data on the association between smoking and symptomatic versus asymptomatic SARS-CoV-2-positive individuals. These studies were included in the meta-analysis of hospitalisation because the study population was the same (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, Singer-Cornelius et al suggested, based on a lack of significant associations between the two conditions in objective tests, that GD and OD are two independent symptoms ( 37 ). A negative correlation has been demonstrated between OD and post-admission severity and mortality of COVID-19 in several studies ( 49 , 50 ), in direct contrast to a report on clinical outcomes by Tabari et al ( 51 ). Speth et al showed that in addition to GD, OD severity was significantly associated with depression and anxiety ( 52 ).…”
Section: Clinical Characteristicsmentioning
confidence: 57%